(untitled) (Texas Journal of Medical Science, 2026)
This article provides an in-depth analysis of the impact of hypothyroidism during pregnancy on child neurodevelopment, particularly autism spectrum disorders (ASD). The effects of thyroid hormone deficiency Considering the epidemiological, mechanistic and clinical aspects, maternal thyroid dysfunction has a cumulative negative impact on fetal brain development. Based on research, risk ratios, treatment efficacy, and environmental factors are discussed, and the need for preventive measures is emphasized. The article is based on a scientific approach, covering a wide range of evidence from animal models to clinical data